The voluntariness in the preschool age: a comparative analysis of various approaches and diagnostic tools - Olga V. Almazova; Daria A. Bukhalenkova; Alexander N. Veraksa (Национальный психологический журнал, 2016)
MMost modern psychologists who deal with preschool age emphasize the development of executive functions as one of the most important factors in this age. The paper compares two most important and common approaches to disclosing and diagnosing voluntariness in the preschool age: the model of executive functions «unity with diversity» of A. Miyake and the skills theory of L.A. Venger. The model of the executive functions considers three main components of executive functions: working memory; flexibility of attention or switching; restraining control. The basis of cognitive abilities theory is the concept of cultural facilities (sensory standards, visual models, etc.) that are being developed throughout the preschool period. In accordance with these two diagnostic complexes were drawn up, aimed at diagnosing voluntariness in preschool years. The study involved 48 children aged 5-6 years, kindergarten students (24 girls and 24 boys) conducted in Moscow, Russia. The results showed that despite a variety of theoretical approaches to early childhood and voluntariness they reverberate the same reality. The most revealing methods (the results of which you can predict the eventual consequences) were elaborated: the method of «Inhibition» (subtest of neuropsychological diagnostic complex techniques NEPSY-II, Korkman et al, 2007) in the case of A. Miyake model, and methods of «Schematization» in the abilities theory of L.A. Venger (Venger, Kholmovskaya, 1978).